2013
DOI: 10.7717/peerj.176
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance and molecular epidemiology ofStaphylococcus aureusfrom Ulaanbaatar, Mongolia

Abstract: This study aimed to characterize Staphylococcus aureus (S. aureus) strains isolated from human infections in Mongolia. Infection samples were collected at two time periods (2007–08 and 2011) by the National Center for Communicable Diseases (NCCD) in Ulaanbaatar, Mongolia. S. aureus isolates were characterized using polymerase chain reaction (PCR) for mecA, PVL, and sasX genes and tested for agr functionality. All isolates were also spa typed. A subset of isolates selected by frequency of spa types was subjecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 74 publications
2
6
0
2
Order By: Relevance
“…2 was from neighbouring Slovakia, but whether he came into contact with Asian immigrants is unknown. Interestingly, those isolates that underwent MLST and spa-typing were t667 [41,42], as was the ST154 strain in the present report.…”
Section: Discussionsupporting
confidence: 58%
“…2 was from neighbouring Slovakia, but whether he came into contact with Asian immigrants is unknown. Interestingly, those isolates that underwent MLST and spa-typing were t667 [41,42], as was the ST154 strain in the present report.…”
Section: Discussionsupporting
confidence: 58%
“…A previous study completed in 4 hospitals of Ulaanbaatar showed 3% MRSA in 207 Staphylococcus aureus strains investigated [40]. A later study reported that among 251 Staphylococcus aureus isolates, methicillin resistance was con rmed in 8.8% of isolates (22/251) [41].…”
Section: Discussionmentioning
confidence: 91%
“…In previous years, limited data available on S. aureus in Mongolia identified a rate of 9% of methicillin resistance and of 28% of multidrug resistance in 2007 and 2011 31 . Sample origin was only known for 21% of isolates in this study.…”
Section: Discussionmentioning
confidence: 99%